The integrated teaching practice of medical cloud dictionary development and project-based learning - Jiayi Zhang; Jiexuan Chen; Hongbin Guo; Wei Liu; Mingzhe Li (BMC Medical Education)
Abstract Objective This study examines a novel teaching model that integrates the development and use of a Medical Cloud Dictionary with project-based learning (PBL). We investigate whether this integrated approach improves teaching effectiveness, enhances student learning outcomes, and reduces teaching pressure compared to traditional PBL. Methods One hundred student volunteers were randomly assigned to an experimental group (n = 50) and a control group (n = 50). Both groups studied seven respiratory-disease-related modules over a single semester (4 months). The experimental group utilized a PBL approach enhanced by the Medical Cloud Dictionary, which provided organized, up-to-date medical information and facilitated collaboration. The control group received traditional PBL-based teaching. Student performance was assessed using theoretical exams, comprehensive case analyses, and clinical practice reports. Feedback questionnaires and interviews were conducted with the experimental group’s students and teachers. Statistical analyses included a Mann-Whitney U-test and chi-square tests to compare outcomes between groups. Results The experimental group demonstrated significantly higher overall scores than the control group (Mann-Whitney U = 22037.5, p < 0.001). Their pass rate reached 100% vs. 98.6% in the control group (χ²=10.145, p < 0.05), and their excellence rate was 22.9% vs. 2.9% (χ²=62.477, p < 0.001). Feedback indicated improved learning efficiency, enhanced independent learning, and reduced teaching pressure. Both students and teachers expressed a desire to continue and expand the integrated mode. Conclusion Integrating a Medical Cloud Dictionary with PBL can stimulate students’ academic engagement, improve their mastery of medical knowledge and practical skills, and foster a stronger desire for independent learning. It also qualitatively enhances teaching quality and strengthens teacher-student relationships. Overall, this integrated teaching model can improve the quality and effectiveness of medical education, benefiting both teachers and students.